Outer membrane protein OmpQ of Bordetella bronchiseptica is required for mature biofilm formation - Cattelan, Natalia (2016)
Bordetella bronchiseptica, an aerobic Gram-negative bacterium, is capable of colonizing the respiratory tract of diverse animals and chronically persists inside the hosts by forming biofilm. Most known virulence factors in Bordetella species are regulated by the BvgAS two-component transduction system. The Bvg-activated proteins play a critical role during host infection. OmpQ is an outer membrane porin protein which is expressed under BvgAS control. Here, we studied the contribution of OmpQ to the biofilm formation process by B. bronchiseptica. We found that the lack of expression of OmpQ did not affect the growth kinetics and final biomass of B. bronchiseptica under planktonic growth conditions. The DompQ mutant strain displayed no differences in attachment level and in early steps of biofilm formation. However, deletion of the ompQ gene attenuated the ability of B. bronchiseptica to form a mature biofilm. Analysis of ompQ gene expression during the biofilm formation process by B. bronchiseptica showed a dynamic expression pattern, with an increase of biofilm culture at 48 h. Moreover, we demonstrated that the addition of serum anti-OmpQ had the potential to reduce the biofilm biomass formation in a dose-dependent manner. In conclusion, we showed for the first time, to the best of our knowledge, evidence of the contribution of OmpQ to a process of importance for B. bronchiseptica pathobiology. Our results indicate that OmpQ plays a role during the biofilm development process, particularly at later stages of development, and that this porin could be a potential target for strategies of biofilm formation inhibition.